Sandwich Structure Bending Analysis using Finite Element Analysis - Mobark, Haidar Faisal Helal; Mothanna Taha Mohammed Fattah Agha; Lekaa Hammed; Sarkaut Ahmed Ameen (Indonesian Journal Publisher, 2025)
Many commercial packages use sandwich composite materials, and this search takes advantage of ANSYS software to evaluate their bending behaviors. FEM gives a good understanding of material behavior with the exposure of outdoor forces. The construction of the sandwich production that accounts for its many layers, as well as for the characteristic features of the materials used is an important aspect of this examination. Many commercial packages use sandwich composite materials, and this search takes advantage of ANSYS software to evaluate their bending behaviors. FEM gives a good understanding of material behavior with exposure to outdoor forces. The construction of the sandwich production that accounts for its many layers, as well as for the characteristic features of the materials used is an important aspect of this examination.